Kompleksnost vzvodov strategije prodajnih poti v izvoznem trženju - Jurše, Milan (Akademija MM, 2012)
Research doesn't treat distribution only as a marketing mix component, but also as a strategic dimension of market position development in foreign markets, which aim is not only to ensure the sale of a company's products, but also to create a distribution system that will provide sales growth and strengthen a firm's competitive advantage in the marketplace. Based on a sample of Slovenian manufacturing firms, this paper examines the relationship between a firm's export market orientation, innovation, relationships with customers in foreign markets, manufacturer brand and retailer brand respectively and its sales channel strategy. The study confirms a positive link of these dimensions of the marketing process with the creation of a manufacturer's successful sales channel strategy in a process of building lasting partnership with independent distributors on foreign markets.
Keywords: blagovne znamke; globalizacija; globalization; izvoz; marketing; mednarodni marketing; prodaja; trženje